Exile, memory and history in the Nineteenth Century: The case of the Chileans in the city of Lima, and their use of the El Comercio newspaper - Hernández Serrano, Cristóbal (2020)
This paper falls within the historical studies on exile in Latin America. It is proposed that, the Chileans exiled during Manuel Montt’s government (1851-1861) who lived in the city of Lima, used the press as a tool, to build a historical account that sought to provide them of a common identity with a double purpose. First, as a way of presentation and defense against the Peruvian public opinion, in a context in which their presence as a group was openly criticized. On the other hand, nineteenth-century press circulation through communication lines also allowed the construction of a narrative by the exiles against the Chilean government.  An ideological conflict that opposed liberal and conservatives positions after the influence of the European revolutions of 1848.